304 The Contribution of Whole Platelet Aggregometry to the Endovascular Management of Unruptured Aneurysms: An Institutional Experience. (August 2016) - Welch, Babu Guai; Aoun, Salah G.; Pride, G. Lee; Rickert, Kim L.; White, Jonathan A.; Hoes, Kathryn; Novakovic, Robin; Sarode, R.
Abstract : INTRODUCTION: Stent-assisted coiling of intracranial aneurysms is a viable and efficient treatment alternative to surgical clipping but requires prolonged antiplatelet therapy. Some patients can be nonresponsive to aspirin and/or clopidogrel. This is the first study analyzing the implications of this assessment using the "whole blood aggregometry (WBA) by impedance" technique. METHODS: The Southwestern Tertiary Aneurysm Registry (STAR) was reviewed between 2002 and 2012 for patients with unruptured aneurysms treated with stent-assisted coiling. The study population was divided into patients who were tested preoperatively for platelet responsiveness to aspirin and clopidogrel ("tested" patients) and those who were not ("nontested" patients). Where necessary, a majority of tested patients received additional doses of antiplatelet drugs to achieve adequate platelet inhibition. End points included the incidence of antiaggregant nonresponsiveness, the rates of thrombotic and hemorrhagic complications, and the rates of permanent morbidity and mortality. RESULTS: A total of 266 patients fulfilled our selection criteria. There were 114 nontested patients who underwent 121 procedures, and 152 tested patients who underwent 171 procedures. The 2 groups did not vary significantly in patient age, sex, and aneurysms location. Aspirin nonresponsiveness was detected in 3 patients (1.75%) and clopidogrel nonresponsiveness was detected in 21 patients (12.3%). Nontested patients had an 11.5% rate of thrombotic complications with a 4.23% permanent morbidity or mortality rate vs 2.3% and 0.58% in tested patients ( P = .001). The incidence of hemorrhagic complications was similar between the 2 groups. CONCLUSION: Preoperative platelet inhibition testing using WBA can be useful to assess and correct antiaggregant nonresponsiveness, and may reduce postoperative mortality and permanent morbidity.